Early onset of neoplasia in the prostate and skin of mice with tissue-specific deletion of Pten - Backman, Stéphanie A. (National Academy of Sciences, 2004)
PTEN is a tumor suppressor gene mutated in various advanced human neoplasias, including glioblastomas and prostate, breast, endometrial, and kidney cancers. This tumor suppressor is a lipid phosphatase that negatively regulates cell survival and proliferation mediated by phosphatidylinositol 3-kinase/protein kinase B signaling. Using the Cre–loxP system, we selectively inactivated Pten in murine tissues in which the MMTV-LTR promoter is active, resulting in hyperproliferation and neoplastic changes in Pten-null skin and prostate. These phenotypes had early onset and were completely penetrant. Abnormalities in Pten mutant skin consisted of mild epidermal hyperplasia, whereas prostates from these mice exhibited high-grade prostatic intraepithelial neoplasia (HGPIN) that frequently progressed to focally invasive cancer. These data demonstrate that Pten is an important physiological regulator of growth in the skin and prostate. Further, the early onset of HGPIN in Pten mutant males is unique to this animal model and implicates PTEN mutations in the initiation of prostate cancer. Consistent with high PTEN mutation rates in human prostate tumors, these data indicate that PTEN is a critical tumor suppressor in this organ.